An improved social force model for improving pedestrian avoidance by reducing search size - Zhihai, Tang; Longcheng, Yang; Jun, Hu; Xiaoning, Li; Lei, You (Physica A, 2024)
In order to solve the slow simulation speed of the social force model in complex indoor scenes, an improved social force model is proposed to reduce the iteration scale of obstacles. The proposed model takes into account the factor of a person’s field of view (FOV) in indoor scenes, and the acting force between pedestrians and obstacles in the social force model is improved to find the optimal number of obstacle iterations without affecting the pedestrian movement law in the traditional model, so as to accelerate the simulation speed. The self-built simulation platform and real evacuation experiments are used to compare the performance indicators of traditional and optimized models and to analyze the relationship between scene complexity and machine computing efficiency. The results show that the optimized model takes less time to predict the evacuation path than traditional models, and as the number of initial pedestrians and obstacles increases, the proportion of machine computation time between the two models will gradually increase. Second, the CPU computation time of the optimized model increases gently, indicating better stability. Therefore, reducing the obstacle iteration scale based on the pedestrian’s FOV factor provides an effective method to solve the slow simulation speed of traditional models. •The use of pedestrian vision factors shortens the size of obstacle iterations in social force modeling calculations.•The improved model has less impact on the evacuation metrics and pedestrian movement patterns of the traditional model.•The improved model promotes a reduction in simulation time compared to the traditional model.•The computational performance of the improved model performs well in complex scenarios.